HLA-B*13:01 is associated with salazosulfapyridine-induced drug rash with eosinophilia and systemic symptoms in Chinese Han population. (August 2014) - Yang, Fanping; Gu, Bo; Zhang, Lirong; Xuan, Jiekun; Luo, Heng; Zhou, Peng; Zhu, Qinyuan; Yan, Sijia; Chen, Sheng-an; Cao, Zhihao; Xu, Jinhua; Xing, Qinghe; et al.
Aim : Salazosulfapyridine (SASP) frequently causes several adverse reactions, such as drug rash with eosinophilia and systemic symptoms (DRESS). This study aims to assess whether there is an association between SASP-induced DRESS and HLA-A, -B and -C alleles in the Chinese Han population.Subjects & methods: We performed an association study of six subjects with SASP-induced DRESS, 30 SASP-tolerant patients and 283 general subjects from the human MHC database, all of whom are Han Chinese.Results : The frequency of the SASP-induced DRESS patients carrying the HLA-B*13:01 allele is 66.67% (4/6). It is significantly higher compared with the general Chinese Han population (15.19%, 43/283; odds ratio: 11.16; p = 0.007) or with the SASP-tolerant patients (13.33%, 4/30; odds ratio: 13.00; p = 0.004).Conclusion : These findings show for the first time that in the Chinese Han population, HLA-B*13:01 is associated with SASP-induced DRESS. HLA-B*13:01 might serve as a potential genetic marker for reducing the prevalence of SASP-induced DRESS. Original submitted 18 December 2013; Revision submitted 31 March 2014